Agroforestry lexicon in Manggarai language: an effort to revitalize culture and empower indigenous peoples - Salimulloh T. Sanubarianto; Mardiyono; Akmal; Yurika F. Wardhani; Mochammad T. Atmodjo; Deden G. Nugraha; Kaprawi Rahman; Maria Rosalinda Talan; Magfirotul Hamdiah; Agik Nur Efendi; Abdul Rahman Arsyad; Sukardi; et al. (Cogent Arts & Humanities)
The decline in forest benefits recognition caused local wisdom on agroforestry technology to fade, threatening the Manggarai people’s identity as a community living harmoniously with forests. The loss of the agroforestry lexicon jeopardizes not only linguistic diversity but also the traditional ecological knowledge embedded within it. Without revitalization, sustainable agroforestry practices balancing agriculture and forest conservation may vanish, further endangering the local environment. This research identifies the agroforestry lexicon of the Manggarai people, using their communication as the data source. Employing ethnographic methods, data were collected through observation, interviews, and elicitation with the Ruteng Pu’u community. Participatory observation of their farming life, in‑depth interviews, and targeted elicitation yielded 253 agroforestry‑related lexicons absent from the Indonesian language. These lexicons fall into three categories: (1) nouns for agroforestry plants, (2) nouns for agroforestry tools, and (3) verbs for agroforestry stages. The findings reveal that agroforestry lexicons are an integral, albeit archaic, part of the Manggarai language. This study contributes to environmental conservation by documenting lexicons essential for sustainable farming and forest management practices.